THE THEORY OF THE KNOWLEDGE GAP - Zdravko Šorđan (Media, Culture and Public Relations, 2020)
In the process of overcoming the knowledge gap we need to begin from the fact that interest in societal problems and societal events does not develop automatically in people at ali. Family and free time subjectively seem closer to people. To this we need to add that people with a lower level of education find it difficult to establish a personal relationship toward complex societal situations and complex societal problems, which would awaken an interest in searching for and receiving information on them. In order for this relationship toward information to be activated it is necessary, among other things, to theoretically and practically research the phenomenon of active search for, and reception of, information. Searching for information is constantly linked to subjectively seen and experienced events and problems, which treat mass media based on the usefulness of information. Therefore, it is a task of primary importance for the mass media to present societal problems to various social groups as subjective problems. In relation to the topic of the mass media, people with a higher level of education have an advantage because their general knowledge is at the same time their for knowledge or previously gained information. Such persons will accept the presented subject easier. Apart from that, existing foreknowledge acts stimulatingly and activates the search for information, while weaker of nonexistent for knowledge is de-stimulating in this sense, so those persons remain without a stance, and with that, also without a behaviour and orientation in life.